Comparison of measurements of time outdoors and light levels as risk factors for myopia in young Singapore children - Dharani, R.; Lee, C.; Theng, Z.; Drury, Vicki; Ngo, C.; Sandar, M.; Wong, T.; Finkelstein, E.; Saw, S. (Nature, 2012)
Aims: To compare methods to measure time outdoor and light levels, two possible predictors of myopia, in Singapore children. Methods: Outdoor time from a diary and portable light meter over a 1-week period was compared in 117 Singapore children aged 6–12 years with and without myopia. All children wore a (HOBO Pendant temp/light Part # UA-002-64) light meter for 1 week and the parents filled the 7-day outdoor diary to track the outdoor activity. Results: Mean outdoor time from diary and time with light levels was 5.44 hours per week and 7.91 hours per week, respectively, during school term and school holidays. Time spent with light levels of >1000 Lux from the light meter were 7.08 h per week and 9.81 h per week, respectively, during school term and school holidays. The intraclass correlation coefficients were 0.21 and 0.28 for outdoor time from the diary and light meter (1000 Lux cut-off) during the school term and holidays, respectively. The correlation coefficient was 0.34 (95% CI 0.05, 0.58) for a weekday during school holidays, 0.17 (−0.14, 0.45) for a weekday during school term, 0.07 (−0.16, 0.29) for a weekday during school term, and 0.25 (0.02, 0.46) for a weekend during school term. Conclusions: The agreement between the light meter and 1-week diary was poor to fair. Both instruments measure different parameters, time outdoors and light intensity, and could therefore capture different aspects of risk in future myopia studies.